2011
DOI: 10.1177/1559827611410266
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Physical and Mental Health Consequences of Child Abuse and Neglect and Implications for Practice

Abstract: The term parent includes custodial and noncustodial parents. †The terms maltreatment and abuse are often used interchangeably in the literature. However, in this article, maltreatment is a general term that includes both abuse and neglect; abuse refers explicitly to acts of commission, whereas neglect refers specifically to acts of omission. ‡ 2008 is the most recent year for which statistics are available (US Department of Health and Human Services 4 ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
144
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(151 citation statements)
references
References 139 publications
3
144
0
4
Order By: Relevance
“…14,40 Focusing solely on biology, depression may partially be the consequence of physiological abuse-related changes in brain structures (eg, corpus collosum, hippocampus, amygdala) and the HPA axis, which ultimately impacts behavior and mood. 55,70 For instance, dysregulation of the HPA axis results in increased cortisol levels, which can lead to the breakdown of serotonin, an important neurotransmitter in the regulation of mood. 40 Depression is often identified as an outcome of abuse; however, it may also influence the extent to which abuse adversely impacts a woman's physical health, thereby positioning it as a mediator between abuse and physical health.…”
Section: Depressive Symptomsmentioning
confidence: 99%
“…14,40 Focusing solely on biology, depression may partially be the consequence of physiological abuse-related changes in brain structures (eg, corpus collosum, hippocampus, amygdala) and the HPA axis, which ultimately impacts behavior and mood. 55,70 For instance, dysregulation of the HPA axis results in increased cortisol levels, which can lead to the breakdown of serotonin, an important neurotransmitter in the regulation of mood. 40 Depression is often identified as an outcome of abuse; however, it may also influence the extent to which abuse adversely impacts a woman's physical health, thereby positioning it as a mediator between abuse and physical health.…”
Section: Depressive Symptomsmentioning
confidence: 99%
“…Research on social determinants has focused somewhat less on biology and more on health-risk behaviors as precursors to adult disorders and disease (Leeb et al, 2011). From this perspective, abuse triggers poor coping behaviors in the form of drug and alcohol use, smoking, and risky sexual practices (Widom, Mormonstein, & White, 2006) and these behaviors, in turn, lead to poor health (Springer, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, abuse triggers poor coping behaviors in the form of drug and alcohol use, smoking, and risky sexual practices (Widom, Mormonstein, & White, 2006) and these behaviors, in turn, lead to poor health (Springer, 2009). The misuse of drugs and alcohol can increase the risk of accidents from overdose and impaired functioning, which can have even more immediate impacts on physical health than would naturally occur if these harmful behaviors are sustained over many years (Leeb et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 These results can be explained by that children exposure to high degrees of trauma as physical or sexual abuse may leads to over activation of the brain neurological pathways which are responsible for "fight or flight" response, frequent exposure for prolonged timesespecially at periods of critical brain developmentmakes the brain chemically organized in a dysfunctional manner, which appears in the form of poor mental and physical state as well as maladaptive behaviors (aggression); mood disorders (anxiety, depression); somatization and posttraumatic stress disorder. 35 The current study concluded that child abuse is a serious problem in our culture and is associated with later psychological disorders. These results can support the concept that the activities of child abuse prevention can play a role in decreasing the rate of psychological disorder in the community.…”
mentioning
confidence: 99%